Use of bioactive glass doped with magnesium or strontium for bone regeneration: A rabbit critical-size calvarial defects study - Nasrin Esfahanizadeh; Mostafa Montazeri; Mohammad Reza Nourani; Mohammad Harandi (Wolters Kluwer Medknow Publications, 2022)
Background: This study aimed to evaluate the amount of bone regeneration in critical defects of rabbit calvaria filled with magnesium- and strontium-doped bioactive glasses. Materials and Methods: In this rabbit critical-size calvarial defects study, 12 male New Zealand white rabbits were randomly divided into two groups. On the calvaria of each rabbit, four lesions (two lesions in the frontal bone and two lesions in the peritoneal bone) were created with a diameter of 8 mm spaced apart. Each lesion was filled in with (1) strontium-doped bioactive glass, (2) magnesium-doped bioactive glass, (3) 45S5 bioactive glass, and (4) empty lesion (control). Six rabbits were sacrificed at the end of 4 weeks, and six rabbits were randomly sacrificed at the end of 8 weeks. Bone sections with a 5-μ thickness of rabbit calvary bone were prepared, and the percentage of new bone, connective tissue, and residual material were calculated in microscopic images. Statistical analysis was performed by two-way ANOVA and Bonferroni additional tests, and the level of significance was set at P < 0.05 in all categories. Results: At 4 weeks, magnesium-doped bioactive glass showed the highest new bone formation with a mean of 11.66 ± 2.64, followed by the strontium-doped bioactive glass with the mean of 11.10 ± 1.69 (P = 0.0001). While at week 8, the highest amount of new bone observed in the strontium-doped group with a mean of 28.22 ± 3.19, and then, the magnesium-doped bioactive glass with a mean of 22.55 ± 3.43 (P = 0.0001). Conclusion: Doping strontium and magnesium in the structure of bioactive glasses increases new bone regeneration in comparison with 45S5 bioactive glass.